2022
DOI: 10.3390/life12081264
|View full text |Cite
|
Sign up to set email alerts
|

The Anti-Tumor Effect of Boron Neutron Capture Therapy in Glioblastoma Subcutaneous Xenograft Model Using the Proton Linear Accelerator-Based BNCT System in Korea

Abstract: Boron neutron capture therapy (BNCT) is a radiation therapy that selectively kills cancer cells and is being actively researched and developed around the world. In Korea, development of the proton linear accelerator-based BNCT system has completed development, and its anti-cancer effect in the U-87 MG subcutaneous xenograft model has been evaluated. To evaluate the efficacy of BNCT, we measured 10B-enriched boronophenylalanine (BPA) uptake in U-87 MG, FaDu, and SAS cells and evaluated cell viability by clonoge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 48 publications
0
7
0
Order By: Relevance
“…The BNCT therapeutic efficacies in vitro and in vivo experiments have been studied at the DM A-BNCT facility. The results were published very recently [50]. For evaluation of the efficacy of BNCT, U-87 MG cells were selected as representative brain cancer, and FaDu and SAS cell lines were chosen for head and neck cancers for in vitro study.…”
Section: Pre-clinical Studymentioning
confidence: 99%
See 4 more Smart Citations
“…The BNCT therapeutic efficacies in vitro and in vivo experiments have been studied at the DM A-BNCT facility. The results were published very recently [50]. For evaluation of the efficacy of BNCT, U-87 MG cells were selected as representative brain cancer, and FaDu and SAS cell lines were chosen for head and neck cancers for in vitro study.…”
Section: Pre-clinical Studymentioning
confidence: 99%
“…Thus, for the U-87 MG, FaDu, and SAS BNCT groups, the results showed that the survival fractions were decreased proportionally depending on BPA treatment concentration and neutron irradiation dose. Figure 22 shows the results of in vitro test for the FaDu cell, which is selected from the reference [50].…”
Section: Pre-clinical Studymentioning
confidence: 99%
See 3 more Smart Citations